2021
DOI: 10.1155/2021/6636152
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and Probiotics Interplay in Amelioration of Ethanol-Induced Oxidative Stress and Inflammatory Response in an In Vitro and In Vivo Model of Hepatic Injury

Abstract: Alcohol-induced liver injury implicates inflammation and oxidative stress as important mediators. Despite rigorous research, there is still no Food and Drug Administration (FDA) approved therapies for any stage of alcoholic liver disease (ALD). Interestingly, metformin (Met) and several probiotic strains possess the potential of inhibiting alcoholic liver injury. Therefore, we investigated the effectiveness of combination therapy using a mixture of eight strains of lactic acid-producing bacteria, commercialize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 72 publications
3
13
0
Order By: Relevance
“…Treatment with five LAB led to the inhibition of SREBP1C and FAS mRNA expression. Our results are consistent with a report by Farhin et al who revealed that probiotics downregulated srebp1c and FAS in HepG2 cells exposed to ethanol [28]. Chronic alcohol consumption impedes lipid oxidation due to erroneous lysosomal biosynthesis, thereby delaying lipid degradation [30].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Treatment with five LAB led to the inhibition of SREBP1C and FAS mRNA expression. Our results are consistent with a report by Farhin et al who revealed that probiotics downregulated srebp1c and FAS in HepG2 cells exposed to ethanol [28]. Chronic alcohol consumption impedes lipid oxidation due to erroneous lysosomal biosynthesis, thereby delaying lipid degradation [30].…”
Section: Discussionsupporting
confidence: 93%
“…By investigating LAB, L. brevis MG5280 and MG5311, L. reuteri MG5458, L. fermentum MG4237, and MG4294 were found to show excellent efficacy at relieving oxidative stress by elevating GSH and antioxidant enzymes. Our results were similar to those obtained with Probiotic V, a product that includes various LAB, which was found to reduce oxidative stress by inhibiting lipid peroxidation and the expression of CYP2E1 in HepG2 cells exposed to ethanol [28]. Moreover, the activity of enzymes, such as AST and ALT, has been reported as one of the most sensitive markers of hepatotoxicity [29].…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the study by Patel et al. ( 139 ) has shown that probiotics and metformin, as well as their combination, can promote M2 polarization and inhibit M1 polarization, contributing to the alleviation of alcoholic liver injury. The role and mechanisms of macrophage polarization in ALD are shown in Table 4 .…”
Section: The Role Of Macrophage Polarization In Liver Diseasesmentioning
confidence: 99%
“…For example, inulin can inhibit short chain fatty acid-induced M1 polarization, and promote M2 polarization, attenuating the inflammation of ALD mice (138). Furthermore, the study by Patel et al (139) has shown that probiotics and metformin, as well as their combination, can promote M2 polarization and inhibit M1 polarization, contributing to the alleviation of alcoholic liver injury. The role and mechanisms of macrophage polarization in ALD are shown in Table 4.…”
Section: Alcoholic Liver Diseasementioning
confidence: 99%
“…Probiotics and postbiotics have emerged as potential nutraceuticals with promises to improve the quality of life and prevent diseases [ 13 ]. Probiotics and postbiotics have also shown promise to rescue the liver from diseases and xenobiotic-induced hepatotoxicity, and restore normal liver functions [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%